Relationship Between Bullying, Victimization, Pro-Social Behaviour and Depresssion among Teenagers in Selangor Malaysia - Uba, Ikechukwu Uzodinma (2009)
The current study examined the relationship between bullying, victimization and prosocial behaviour with depression among teenagers. The study also determined the moderation effect of pro-social behavior on the relationship between the independent and dependent variables. Ecological systems theory and social cognitive theory were used to highlight the assumptions of the study. The respondents of the study were 242 teenagers from selected secondary schools in Selangor, Malaysia, aged between 13-17 years (mean = 14.67 years; s.d = 1.27). Simple random sampling technique was used to identify the respondents. Peer Relationship Questionnaire (PRQ) by Rigley and Slee (1993) was used to assess bullying, victimization and pro-social behaviour among respondents of the study. The Children Depression Inventory (CDI) (Kovac, 1985) was used to measure depression. Descriptive statistics, t-test, regression and simple factorial ANOVA were used in data analysis. The findings of the study indicated that there was a significant difference (t = 3.306, p ≤ .05) in bullying between male and female teenagers. The study also indicated that depression has a significant and positive correlation with both bullying (r = .296, p ≤.01) and victimization (r = .432, p ≤ .01). Also, the study found significant and positive correlation between bullying and victimization (r = .422, p ≤ .01). Pro-social behaviour was found to have a positive correlation with victimization only (r = .148, p ≤ .05). Victimization was the only unique predictor of depression (Beta = .373, p ≤.0001) in peer relationships. Findings of the study equally revealed that pro-social behaviour does not moderate the relationship between bullying, victimization and depression. The findings of the study lend support to the theory of Bronfenbrener (1979) and Bandura (1963) in that depression can be caused by the socioenvironment, and that bullying, victimization and pro-social behaviour can all be learned from the environment. It also adds to the understanding of peer relationship among teenagers, by emphasizing the need for psychological treatment for identified bullies, victims and depressed teenagers. The study suggested that future research need to expand beyond the self report of internalizing and externalizing depression reported by the teenage respondents. The self report from parents and teachers should also be included as part of the assessment of teenagers.